Efficacy of D, L-methadone in the treatment of glioblastoma in vitro. (19th June 2018) - Brawanski, Konstantin; Brockhoff, Gero; Hau, Peter; Vollmann-Zwerenz, Arabel; Freyschlag, Christian; Lohmeier, Annette; Riemenschneider, Markus J; Thomé, Claudius; Brawanski, Alexander; Proescholdt, Martin A
Aim: Recently, D, L-methadone has been put forward as adjuvant treatment in glioblastoma (GBM).Methods: We analyzed the μ-opioid receptor expression in a set of GBM cell lines and investigated the efficacy of D, L-methadone alone and in combination with temozolomide (TMZ).Results & conclusion: Expression of the μ-opioid receptor was similar in the tested cell lines. High concentrations of D, L-methadone induced apoptosis in all cell lines and showed treatment interaction with TMZ. However, in lower dosages, reflecting clinically attainable concentrations, D, L-methadone alone showed no efficacy, and induced even higher proliferation in one specific cell line. Also, no interaction with TMZ was observed. These results suggest caution to the premature use of D, L-methadone in the treatment of GBM patients.